Parents’ awareness of the psychological and social characteristics Of their children with Autism Spectrum Disorder (ASD) - Fares , Oumhani (Journal of Science and Knowledge Horizons, 2025)
This study aimed to investigate the level of awareness among parents of children with autism regarding the psychological and social characteristics of their children. The researcher employed the descriptive-analytical approach, utilizing a form designed by Al-Hammad (2015) to assess the psychological and social traits of autistic children. The form was administered to 63 parents, including 33 fathers, whose children attend the EL-Shorouq Center in the Ain Defla province. The results indicated a high level of awareness among both parents, with consistent awareness levels across different types of characteristics. The study also recommended certain measures to further enhance this awareness, emphasizing its importance in the care and support of these children